Association of Echocardiographic Findings with in-Hospital Mortality of COVID-19 Patients and Their Changes in One-Month Follow-Up; a Cohort Study - Mosallami Aghili, Seyed Morsal; Khoshfetrat, Mehran; Asgari, Ali; Arefizadeh, Reza; Mohsenizadeh, Aboulfazl; Mousavi, Seyyed Hossein (Archives of Academic Emergency Medicine, 2022)
Introduction: Evidence showed that cardiac complications may occur in coronavirus disease-19 (COVID-19) during the acute and post-infection phases. This study aimed to evaluate the association between the echocardiographic characteristics and in-hospital mortality of COVID-19 patients as well as the changes after one-month follow-up. Method: All adult (≥18 years old) hospitalized COVID-19 patients in need of echocardiography based on the guideline of the Iranian Society of Echocardiography for performing various types of echocardiography during the COVID-19 pandemic were included in this study. An expert cardiologist performed the echocardiography on all patients and also on all available patients one month after discharge. Results: 146 hospitalized cases of COVID-19 and 81 cases available for 1-month follow-up echocardiography were studied in this prospective study. Left ventricle wall hypokinesia, aorta valve stenosis, dilated Inferior Vena Cava (IVC), and Pulmonary Artery Systolic Pressure (PASP) of more than 35 were associated with 3.59 (95% CI: 1.19-10.79, p = 0.02), ‎11 (95% CI: 3.3 – 36.63, p = 0.001), ‎5.58 (95% CI: 1.04-29.41, p = 0.041)‎, and 2.91 (95% CI: 1.35 – 6.3, p = 0.001) times higher odds of mortality than healthy subjects. In 1-month follow-up of patients, deterioration in LVEF (p = 0.03) was detected in the not-fully vaccinated patients, and a significant decrease in PASP was observed in all cases (p = 0.04); but these changes were not clinically important. Conclusion: Left ventricle wall hypokinesia, aorta valve stenosis, dilated IVC, and PASP ≥ 35 were predictors of in-hospital mortality in our study. There were not any potential clinically significant differences in one-month echocardiographic follow-ups of the studied patients.